Identification of bi-allelic KIF9 loss-of-function variants contributing to asthenospermia and male infertility in two Chinese families - Meng, Zhixiang; Meng, Qingxia; Gao, Tingting; Zhou, Hui; Xue, Jiajia; Li, Hong; Wu, Yibo; Lv, Jinxing (Frontiers in Endocrinology, 2023)
Introduction Asthenozoospermia (AZS) is a leading cause of male infertility, affecting an estimated 18% of infertile patients. Kinesin proteins function as molecular motors capable of moving along microtubules. The highly conserved kinesin family member 9 (KIF9) localizes to the central microtubule pair in the flagella of Chlamydomonas cells. The loss of KIF9 expression in mice has been linked to AZS phenotypes. Methods Variant screening was performed by whole exome sequencing from 92 Chinese infertile patients with AZS. Western blot was used to was used for analyzing of candidate proteins expression. Patients’ sperm samples were stained with immunofluorescent to visualise proteins localization and were visualised by transmission electron microscopy (TEM) to determine axoneme structures. Co-immunoprecipitation assay was used to verify the binding proteins of KIF9. In vitro fertilization (IVF) was used to evaluate the efficiency of clinical treatment. Results Bi-allelic KIF9 loss-of-function variants were identified in two unrelated Chinese males exhibiting atypical sperm motility phenotypes. Both of these men exhibited typical AZS and suffered from infertility together with the complete absence of KIF9 expression. In contrast to these KIF9-deficient patients, positive KIF9 staining was evident throughout the flagella of sperm from normal control individuals. KIF9 was able to interact with the microtubule central pair (CP) component hydrocephalus-inducing protein homolog (HYDIN) in human samples. And KIF9 was undetectable in spermatozoa harboring CP deletions. The morphologicy of KIF9-deficient spermatozoa appeared normal under gross examination and TEM. Like in mice, in vitro fertilization was sufficient to overcome the fertility issues for these two patients Discussion These findings indicate that KIF9 associates with the central microtubules in human sperm and that it functions to specifically regulate flagellar swinging. Overall, these results offer greater insight into the biological functions of KIF9 in the assembly of the human flagella and its role in male fertility.